UZBEK AND RUSSIAN PEOPLE'S NATIONAL CEREMONIES (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
we have provided information about the national ritual ,Customs and traditions of the Uzbek and Russian nation and their similarities in this article